Wpływ uziarnienia gleby na bonitację drzewostanów sosnowych w południowo-zachodniej Polsce - Sewerniak, Piotr (Leśne Prace Badawcze, 2011)
The study was conducted in 349 Scots pine ( Pinus sylvestris L.) stands comprising two soil moisture groups – non-gleyic (273 plots) and gleyic (76). In every plot, the site index of a Scots pine stand was determined as mean height of the ten thickest trees per 0.1 hectare, called the „top height”. The top height was recalculated for a base-age of 100 years (H100), however this indicator was biased in relation to stand age. The bias was removed using a regression model, and then the obtained site index (B) ceased to be related to stand age. Soil texture data was already available from the forest service of the State Forests National Forest Holding. For each stand the weighted mean value of every soil textural class was calculated. The site index was positively correlated with the texture fraction 1 mm had the opposite effect on site index for each soil group (negative on non-gleyic and positive on gleyic soils). The results (height growth) show that Scots pine most effectively utilizes soil nutrient resources when grows on sandy soils and that the species does not utilize the potentially greater nutrients retention by clay soils. On sandy soils the positive influence on pine growth of increasing the composition of fine fractions was caused more by the beneficial effect of their moisture retention (water sorption) than any nutritional role.